"Memória do fogo: o século do vento", de Eduardo Galeano : memória e resistência das mulheres nas ditaduras latino- americanas - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The register of the official history, in particular the history of what is called the new world, is a mosaic full of gaps based in one-sided narratives that generally show how goodie was the presence of the European colonizer to the social and cultural development of the native population that originally occupied these countries and had a great deal of their culture slaughtered by the massive economic exploration resident at the Continent since the XVI century. Observant to the most secret and forgotten voices, the Uruguayan writer and journalist Eduardo Galeano evidences over his work the subjects or agents neglected by the official registers. In the trilogy Memoria de Fogo, he rewrites from another point of view the history of Latin America throughout the process of the European colonization. At the last part of the work, destined to the XX century, called by the author O século do vento, he is dedicated particularly to the reports of the personages that suffered the violence and the abuse of the power imposed by the dictatorships that permeates with suffering and pain the period between 1964 and 1985, with special emphasis to the actions by the women, often ignored and silenced by the history, but = developed a decisive role to the reestablishment of the democracy at the countries that were victimized by the dictatorships. This research was motivated to by the singularity of the representation of the female protagonism related to the reality of Latin American dictatorships, which aroused the desire and motivation literature research on Galeano's work. In view of the investigation of the problem that permeates this research, the memory and resistance of women in Latin American dictatorships, it started from the bibliographical study, aiming to understand the resources used by Eduardo Galeano to compose the narratives that present as motivating axes to history and memory, of women's activism. The research focused on the search for understanding how the author, in the book Memória do Fogo: o século do fogo (1998), the aim of this research, manages to use female protagonism, through literature, to bring his memories to the surface of the historical-literary discourse, aiming to infer how, through the historical literary narrative, the construction of female representation and activism in the Latin American context takes place. In the analysis carried out, it was possible to conclude that the speeches, popular actions, union and resistance movements organized and experienced by these women were primordial to the end of the Latin American dictatorship
Eduardo Galeano's "Memory of fire: the Ccentury of the wind": women's memory and resistance in latin american dictatorships.
Keywords: Eduardo Galeano; Memória; Resistência; Mulheres; Ditaduras latino- americanas; Memory; Resistance; Women; Latin American dictatorships; LINGUISTICA, LETRAS E ARTES::LETRAS; LETRAS::LINGUAS ESTRANGEIRAS MODERNAS